PENGGUNAAN MODEL THINK TALK WRITE DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA TENTANG BANGUN RUANG PADA SISWA KELAS IV SD NEGERI 2 KALIREJO TAHUN AJARAN 2015/2016 - Rosandi, Upi (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Think Talk Write Model Using Concrete Media in Improving Mathematics Learning about Geometry for the Fourth Grade Students of SD Negeri 2 Kalirejo in the Academic Year of 2015/2016. The objectives of this research is to improve Mathematics learning about geometry for the fourth grade students. Subjects of the research were fourth grade students of SD Negeri 2 Kalirejo in academic year of 2015/2016 totaling 31 students. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted two meetings including planning, action, observation, and reflection. The results of this research showed that the use of Think Talk Write model using concrete media can improve Mathematics learning about characteristics of geometry. Keywords: TTW, concrete media, Mathematics Abstrak: Penggunaan Model Think Talk Write Dengan Media Konkret dalam Peningkatan Pembelajaran Matematika Tentang Bangun Ruang pada Siswa Kelas IV SD Negeri 2 Kalirejo Tahun Ajaran 2015/2016. Tujuan penelitian ini yaitu: untuk meningkatkan pembelajaran matematika tentang bangun ruang pada siswa kelas IV. Subjek penelitian ini adalah siswa kelas IV SDN 2 Kalirejo tahun ajaran 2015/2016 yang berjumlah 31 siswa. Penelitian ini merupakan Penelitian Tindakan Kelas kolaboratif yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari empat tahapan yaitu perencanaan, pelaksanaan, observasi, refleksi. Hasil penelitian menunjukkan penggunaan model TTW dengan media konkret sesuai dapat meningkatkan pembelajaran matematika tentang sifat-sifat bangun ruang. Kata Kunci: TTW, Media Konkret, Matematika